Multiobjective optimisation of a Brazilian BECCS using exergy - Rodrigues, Luis Adolfo Mazini (2024)
One of the essential strategies to maintain a safe global temperature anomaly under 1.5 °C is using Negative Emission Technologies (NETs). Bioenergy with Carbon Capture and Storage (BECCS) is a NET that captures CO2 emitted by an industrial bioenergy plant and stores it in geological reservoirs. The issue is that the energy consumption to capture carbon dioxide could make this technology unfeasible. This thesis investigates the exergetic impact of integrating an oxy-combustion Carbon Capture and Storage (CCS) system into a Brazilian sugarcane biorefinery, encompassing first- and second-generation ethanol production, anaerobic digestion, and biogas cleaning. A multiobjective optimisation approach incorporating exergy analysis was employed to evaluate the system\'s performance and carbon sequestration potential across various industrial and uncontrollable parameters. Results indicate that while CCS can significantly capture CO2 emissions from the industry, its integration imposes a substantial exergy penalty, primarily driven by the air separation and CO2 compression subsystems. The study highlights the trade-offs between electricity self-sufficiency and CO2 capture efficiency, revealing that only a small fraction of optimal configurations achieved net electricity export. Furthermore, directing lignocellulosic materials such as bagasse and straw towards combustion rather than 2G ethanol production could enhance the overall system optimally. These findings underscore the need for technological advancements and strategic management to mitigate the exergetic costs associated with CCS implementation in the Brazilian sugarcane industry, supporting the country\'s carbon reduction targets and contributing to the global effort to limit climate change.